2015
DOI: 10.3390/en8088887
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrogen-Based Storage Systems on Self-Consumption and Self-Sufficiency of Residential Photovoltaic Systems

Abstract: This paper analyzes the behavior of residential solar-powered electrical energy storage systems. For this purpose, a simulation model based on MATLAB/Simulink is developed. Investigating both short-time and seasonal hydrogen-based storage systems, simulations on the basis of real weather data are processed on a timescale of 15 min for a consideration period of 3 years. A sensitivity analysis is conducted in order to identify the most important system parameters concerning the proportion of consumption and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Mulder et al [9] investigated seven Belgian households and showed that the optimal storage size (based on their own definition and given in kWh storage per annual PV electricity in MWh) was in the range of 0.4-1.5. Pötzinger et al [10] modeled a household PV system coupled with hydrogen storage in Germany and showed that for a PV installation of 8.6 kWp, 8 kWh of storage would increase PV electricity self-consumption by 35 percentage points. Several other studies have also presented results concerning self-consumption and self-sufficiency of PV-battery system for German and Belgian households, e.g., Linssen et al [11], Beck et al [12], Johann and Madlener [13], de Oliveira e Silva and Hendrick [14], Braun et al [15], and Schreiber and Hochloff [16].…”
Section: Introductionmentioning
confidence: 99%
“…Mulder et al [9] investigated seven Belgian households and showed that the optimal storage size (based on their own definition and given in kWh storage per annual PV electricity in MWh) was in the range of 0.4-1.5. Pötzinger et al [10] modeled a household PV system coupled with hydrogen storage in Germany and showed that for a PV installation of 8.6 kWp, 8 kWh of storage would increase PV electricity self-consumption by 35 percentage points. Several other studies have also presented results concerning self-consumption and self-sufficiency of PV-battery system for German and Belgian households, e.g., Linssen et al [11], Beck et al [12], Johann and Madlener [13], de Oliveira e Silva and Hendrick [14], Braun et al [15], and Schreiber and Hochloff [16].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies in literature are based on artificial grid topologies [39], characteristic household loads [40], and simulated PV generation [41]. Instead, we apply real data for the low-voltage distribution grid topology, the household loads, and the distributed generation from photovoltaics to allow for results close to reality.…”
Section: Simulation Setupmentioning
confidence: 99%
“…Owing to the low ratio of electricity provided by the PV module to the electricity demand, only short‐term storage but no seasonal storage is possible for the MFH (see Table ). In the case of the SFH, the situation is more complex: there is the possibility of seasonal storage in addition to short‐term storage . The different design of the PV plant (a third relative to that of the MFH) in combination with the lower load demand (only a ninth relative to that of the MFH) enables an annual energy surplus and results in a considerably lower self‐consumption share (see Table ).…”
Section: Resultsmentioning
confidence: 99%